2020
DOI: 10.11648/j.rs.20200501.11
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Successful Rehabilitation and Return to Play for a D1 Gymnast After Treatment for Lateral Epicondylosis with Ultrasound Guided Percutaneous Tenotomy (Tenex)

Abstract: Lateral elbow pain is a commonly seen in sports medicine. There are multiple interventions for this chronic condition which may lead to difficulty with successful treatment. There are also multiple rehabilitation strategies employed for treatment. Variations in treatments and rehabilitation protocols can lead to different and sometimes unsuccessful long term outcomes. We present a novel case of a Division 1 college gymnast with recalcitrant lateral elbow pain who underwent percutaneous tenotomy (Tenex) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…By operating in a closed fluid system, normal tissue is not affected by the procedure ( Morrey, 2014 ; Kamineni et al , 2015 ; Morrey, 2018 ). As demonstrated in humans, the procedure is safe and well-tolerated ( O’Daly et al , 2009 ; Morrey, 2018 ; Walrod et al , 2020 ). Horses in this study demonstrated improvement with no adverse events, and complete resolution of lameness in 8 of 10 treated limbs following a single treatment.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…By operating in a closed fluid system, normal tissue is not affected by the procedure ( Morrey, 2014 ; Kamineni et al , 2015 ; Morrey, 2018 ). As demonstrated in humans, the procedure is safe and well-tolerated ( O’Daly et al , 2009 ; Morrey, 2018 ; Walrod et al , 2020 ). Horses in this study demonstrated improvement with no adverse events, and complete resolution of lameness in 8 of 10 treated limbs following a single treatment.…”
Section: Discussionmentioning
confidence: 87%
“…As of 2023, more than 160,000 human patients have been treated with the Tenex procedure, and fewer than 30 adverse events (mostly localized swelling) requiring medical attention were reported (Morrey B, personal communication, 2023; Tenex Health, Lake Forest, CA, File Data, 2023). The risk/benefit has been exceptional, with efficacy between 80% and 95% following a single procedure performed under local anesthesia ( Avella and Smith, 2012 ; Barnes, 2013 ; Koh et al , 2013 ; Nanos and Malanga, 2015 ; Patel, 2015 ; Morrey, 2017 , 2018 ; Freed et al , 2019 ; Walrod et al , 2020 ). PUD of tendinopathic tissue in human patients has demonstrated the advantage of excising nonstructural debris, thereby allowing regenerative cells to populate the newly cleared space ( Koh et al , 2013 ; Elattrache and Morrey, 2013 ; Barnes et al , 2015 ; Kamineni et al , 2015 ; Patel, 2015 ; Patel et al, 2015 ; Seng et al , 2016 ; Ostrom and Joseph, 2018 ; Freed et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gymnasts have different physical training plans during the preparation period and before the competition. 12 The training method can also use interval training. Preparing for a weekly training plan to increase the intensity of the training.…”
Section: Discussionmentioning
confidence: 99%
“…35 A case report on Tenex in a Division 1 gymnast treated for lateral epicondylitis showed the athlete was able to return to competitive practice in 2 months and did not have recurrence of symptoms for up to 1 year of follow-up. 36 Allowing for appropriate recovery and rehabilitation following percutaneous tenotomy, the complication rate is reported to be low at 0.7%, which includes risks such as infection, postprocedural pain, and partial tendon rupture. 32,37 Overall, the literature suggests long-term success of percutaneous tenotomy but with a delay in RTP to allow for tendon healing and recovery.…”
Section: Percutaneous Tenotomymentioning
confidence: 99%
“…35 A case report on Tenex in a Division 1 gymnast treated for lateral epicondylitis showed the athlete was able to return to competitive practice in 2 months and did not have recurrence of symptoms for up to 1 year of follow-up. 36…”
Section: Percutaneous Tenotomymentioning
confidence: 99%